PENGARUH PENGETAHUAN IBU HAMIL TERHADAP PEMANFAATAN PELAYANAN KESEHATAN GIGI DAN MULUT DI PUSKESMAS KABUPATEN BADUNG - Luh Putu Suarniti (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2014)
It is important for pregnant women to take care their oral health during pregnancy. But the utilization of oral health care services by pregnant wormen in BPG Puskesmas at Badung Regency was very low, it is below than 50%. The purpose of this study is to know the degfee of knowledge of pregnant women about oral health care and its correlation with the utilization of the oral health care service in BPG Puskcsmas at Badung Regency. This was Crosssectional Study, using 106 samples of pregnant women who ANC in Puskesmas at Badung Regence. Data was collecting by interview and then analyzed by descriptive statistic and statistic analytic with chi-Squrye test. This study found that 55% of pregnant women have o good knowledge, and only 40% utillizing oral health care services in Puskcsmas at Badung regency. The conclusion is: utilization of oral health care service influence by knowledge of pregnant women while the attitude does not influence the utilization of oral health care service